Insight into antibiotics removal: exploring the photocatalytic performance of a Fe3O4/ZnO nanocomposite in a novel magnetic sequential batch reactor - Fernández, L. (2019)
The purpose of this research was the preparation and photocatalytic evaluation of a novel nanocomposite (NC) based on Fe3O4/ZnO, to eliminate four persistent antibiotics in surface waters: sulfamethoxazole, trimethoprim, erythromycin and roxithromycin. Prior to the operation of the photocatalytic reactor, the influence of pH (3-9), catalyst concentration (50-800 mg L-1), oxidant dose (0-100 mg L-1) and concentration of different targets (10-100 mu g L-1) on the catalytic efficiency was evaluated. The analysis of reaction kinetics showed that degradation processes of the four antibiotics followed a pseudo-first-order kinetic model. Antibiotics adsorption onto the nanocomposite surface depended on their electrostatic nature and played an important role when decreasing the initial concentration of antibiotics. In this context, kinetic rates were higher at lower initial levels of organic pollutants, which is a favourable effect from a practical application perspective. On the other hand, a synergistic effect of the available Fe in the nanocomposite was found, contributing to the oxidation of antibiotics by photo-Fenton as a secondary reaction. Then, a magnetic photocatalytic reactor was operated under optimal conditions. The enhanced photonic efficiency of Fe3O4/ZnO in the system, as well as the ease of the magnetic separation and catalyst reusability, indicate the viability of this reactor configuration.